Active buoyancy adjustment increases dispersal potential in benthic marine animals. Issue 6 (1st February 2019) - Hamel, Jean‐François; Sun, Jiamin; Gianasi, Bruno L.; Montgomery, Emaline M.; Kenchington, Ellen L.; Burel, Benoit; Rowe, Sherrylynn; Winger, Paul D.; Mercier, Annie
Abstract: While the study of dispersal and connectivity in the ocean typically centres on pelagic species and planktonic larval stages of benthic species, the present work explores an overlooked locomotor means in post‐settlement benthic stages that redefines their dispersal potential. Members of the echinoderm class Holothuroidea colonize a diversity of marine environments world‐wide, where they play key ecological and economical roles, making their conservation a priority. Holothuroids are commonly called sea cucumbers or sea slugs to reflect their slow movements and are assumed to disperse chiefly through pelagic larvae. The present study documents and explores their unexpected ability to actively modify their buoyancy, leading them to tumble or float at speeds orders of magnitudes faster than through benthic crawling. Two focal species representing different taxonomic orders, geographic distributions and reproductive strategies were studied over several years. Active buoyancy adjustment (ABA) was achieved through a rapid increase in water‐to‐flesh ratio by up to 740%, leading to bloating, and simultaneously detachment from the substrate. It occurred as early as 6 months post settlement in juveniles and was recorded in wild adult populations. In experimental trials, ABA was triggered by high conspecific density, decreasing salinity and increasing water turbidity. Based on field video footage, ABA‐assisted movements generated speeds of up to 90 km/day. These findings imply that displacement during planktonic larval stages may not supersede the locomotor capacity of benthic stages, challenging the notion of sedentarity. Combining the present results and anecdotal reports, ABA emerges as a generalized means of dispersal among benthic animals, with critical implications for world‐wide management and conservation of commercially and ecologically significant species. Abstract : This study documents the unexpected ability of so‐called sessile or sedentary benthic marine animals (e.g. sea cucumbers) to actively modify their buoyancy to tumble or float at speeds orders of magnitudes faster than anticipated. These findings redefine the locomotor capacity of benthic animals, challenging the notion of sedentarity, with critical implications for worldwide management and conservation of commercially and ecologically significant species.